Identification of atmospheric circulation schemes that promote summer hail events in the Northern Italy - Vincenzo Capozzi; Alberto Fucci; Giorgio Budillon; Giannetta Fusco; Enrico Arnone; Nicola Cortesi; Giulio Monte; Sante Laviola (Atmospheric Research, 2026)

A consensus-based, revised and comprehensive catalogue for Mediterranean water masses acronyms - KATRIN SCHROEDER; SANA BEN ISMAIL; MANUEL BENSI; ANTHONY BOSSE; JACOPO CHIGGIATO; GIUSEPPE CIVITARESE; FRANCESCO FALCIERI M; GIANNETTA FUSCO; MIROSLAV GAČIĆ; ISAAC GERTMAN; ELISABETH KUBIN; PAOLA MALANOTTE-RIZZOLI; et al. (Mediterranean Marine Science, 2024)
Addressing the need for clear communication in Mediterranean oceanography, this study presents a revised and comprehensive catalogue of water mass acronyms. Although there is no universal set of standard rules for assigning acronyms to water masses, as these can vary among different research groups, regions, or scientific communities, scientists generally aim for clarity and consistency when naming and abbreviating water masses to facilitate communication within the scientific community. The team of experts, guided by the CIESM (the Mediterranean Science Commission) C2 Committee on the Physics and Climate of the Ocean, reviewed existing literature and established new acronyms and naming guidelines. This standardized system, emphasizing clarity and consistency, replaces the current variable practices employed by different research groups.

Ocean-atmosphere-ice processes in the Ross Sea: A review - Pierpaolo Falco; Giuseppe Aulicino; Pasquale Castagno; Vincenzo Capozzi; Paola de Ruggiero; Angela Garzia; Antonino Ian Ferola; Yuri Cotroneo; Alessio Colella; Giannetta Fusco; Stefano Pierini; Giorgio Budillon; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2024)

Factors driving the bioavailability of particulate organic matter in the Ross Sea (Antarctica) during summer - Cristina Misic; Francesco Bolinesi; Michela Castellano; Enrico Olivari; Paolo Povero; Giannetta Fusco; Maria Saggiomo; Olga Mangoni (Hydrobiologia, 2024)
The biochemical composition and bioavailability of particulate organic matter (POM) were studied in relation to abiotic (water column stratification, macronutrient concentrations) and biotic factors (phytoplankton biomass and functional groups) in the open Ross Sea and coastal area of Terra Nova Bay, Antarctica, during the austral summer 2017. The presence of different sub-systems was highlighted by spatial and temporal variations of all the considered variables, characterised by higher concentrations of particulate organic carbon and nitrogen in Terra Nova Bay, where diatoms dominated, while in the open Ross Sea was higher the contribution of haptophytes ( Phaeocystis antarctica Karsten, 1905). The southernmost Ross Sea was characterised by significantly higher concentrations of carbohydrates in the entire water column. High lipid contribution and low photosynthetic activity indicated aged POM, suggesting that POM was composed mainly by the remnants of previous haptophytes production. The higher lability of the carbohydrates indicated that an increase of haptophytes in the area could alter the biogeochemical C cycle, reducing the storage of refractory carbon in the depths, and favouring the transfer and respiration of C in the trophic web, with a decrease of export rate in the Ross Sea.

Atmospheric controls on the Terra Nova Bay polynya occurrence in Antarctica - Ricardo Fonseca; Diana Francis; Giuseppe Aulicino; Kyle S. Mattingly; Giannetta Fusco; Giorgio Budillon (Climate Dynamics, 2023)
Polynyas, or ice-free regions within the sea ice pack, are a common occurrence around Antarctica. A recurrent and often large polynya is the Terra Nova Bay Polynya (TNBP), located on the western side of the Ross Sea just off Victoria Land. In this study, we investigate the atmospheric conditions leading to the occurrence of the TNBP and its spatial variability, as estimated using satellite-derived ice surface temperature and sea ice concentration data. A cluster analysis revealed that katabatic winds descending the Transantarctic Mountains, account for about 45% of the days when the TNBP exceeded its 2010–2017 mean extent plus one standard deviation. Warmer and more moist air intrusions from lower-latitudes from the Pacific Ocean, which are favoured in the negative phase of the Southern Annular Mode, play a role in its expansion in the remaining days. This is more frequent in the transition seasons, when such events are more likely to reach Antarctica and contribute to the occurrence and the widening of the polynya. In-situ weather data confirmed the effects of the mid-latitude air intrusions, while sea ice drifts of up to 25 km day −1 cleared the ice offshore and promoted the widening of the polynya starting from the coastal areas. Knowing the atmospheric factors involved in the occurrence of coastal polynyas around Antarctica is essential as it helps in improving their representation and predictability in climate models and hence advance the models’ capabilities in projecting Antarctic sea ice variability.

Spatial-Related Community Structure and Dynamics in Phytoplankton of the Ross Sea, Antarctica - Francesco Bolinesi; Maria Saggiomo; Francisco Ardini; Pasquale Castagno; Angelina Cordone; Giannetta Fusco; Paola Rivaro; Vincenzo Saggiomo; Olga Mangoni (Frontiers in Marine Science, 2020)
The Ross Sea exhibits the largest continental shelf and it is considered to be the most productive region in Antarctica, with phytoplankton communities that have so far been considered to be driven by the seasonal dynamics of the polynya, producing the picture of what is considered as the classical Antarctic food web. Nevertheless, the Ross Sea is made up of a complex mosaic of sub-systems, with physical, chemical, and biological features that change on different temporal and spatial scales. Thus, we investigated the phytoplankton community structure of the Ross Sea with a spatial scale, considering the different ecological sub-systems of the region. The total phytoplankton biomass, maximum quantum efficiency (Fv/Fm), size classes, and main functional groups were analyzed in relation to physical–chemical properties of the water column during the austral summer of 2017. Data from our study showed productivity differences between polynyas and other areas, with high values of biomass in Terra Nova Bay (up to 272 mg chl a m –2 ) and the south-central Ross Sea (up to 177 mg chl a m –2 ) that contrast with the HNLC nature of the off-shore waters during summer. Diatoms were the dominant group in all the studied subsystems (relative proportion ≥ 50%) except the southern one, where they coexisted with haptophytes with a similar percentage. Additionally, the upper mixed layer depth seemed to influence the level of biomass rather than the dominance of different functional groups. However, relatively high percentages of dinoflagellates (∼30%) were observed in the area near Cape Adare. The temporal variability observed at the repeatedly sampled stations differed among the sub-systems, suggesting the importance of Long-Term Ecological Research (L-TER) sites in monitoring and studying the dynamics of such an important system for the global carbon cycle as the Ross Sea. Our results provide new insights into the spatial distribution and structure of phytoplankton communities, with different sub-systems following alternative pathways for primary production, identifiable by the use of appropriate sampling scales.

Dynamics and Variability of Terra Nova Bay Polynya - Giannetta Fusco; Daniela Flocco; Giorgio Budillon; Giancarlo Spezie; Enrico Zambianchi (Marine Ecology, 2002)
We present a process study on the dynamics and variability of the Terra Nova Bay polynya in the western sector of the Ross Sea. The air‐sea heat exchange is known to be particularly large in polynya during the winter, when differences between air and sea temperatures are large. We apply a 1‐D model (Pease, 1987; Van Woert, 1999a, 1999b), which is modified in the latent heat parameterisation in order to account for time‐dependent relative humidity and cloud coverage. Furthermore, the Ice Collection Depth is correlated linearly with a variable wind speed. The model is forced with two different meteorological data sets: the operational analysis of the European Center for Medium Range Weather Forecasts atmospheric data set and the meteorological parameters measured by an Automatic Weather Station located on the coast of Terra Nova Bay. The results are compared in terms of polynya extension, ice, and High Salinity Shelf Water production. According to the two different wind velocities, the results obtained from the different data sets clearly differ. Qualitatively, however, the results are in good agreement.